Relative team-member exchange, affective organizational commitment and innovative behavior: The moderating role of team-member exchange differentiation - Chen, Chao; Liu, Xinmei (Frontiers in Psychology, 2022)
Based upon social comparison theory, a multilevel moderated-mediation theoretical model was built up to explore the influence mechanism of relative team-member exchange (RTMX) on innovative behavior. We tested the proposed hypotheses using a sample of 260 individual members within 51 teams in a two-wave survey study. Controlling for team-member exchange (TMX), results showed that RTMX was positively related to innovative behavior, and the relationship above was mediated by affective organizational commitment. Moreover, team-level TMX differentiation played a moderating role in the mediated relationship between RTMX and innovative behavior through affective organizational commitment. This study also emphasizes the significance of conceptualizing TMX as concurrently implementing at multiple levels.